2016
DOI: 10.17795/soj-7461
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for an Ultrasonic Bone-Cutting Device in Adult Spinal Deformity: A Safety and Reproducibility Study

Abstract: Background: Ultrasonic bone-cutting devices (UBC) are new cutting tools and have low frequency ultrasonic blade. There is limited data on the safety and effectiveness of using ultrasonic bone-cutting devices in the treatment of adult spinal deformities (ASD). Objectives: This Retrospective review of prospectively collected data was designed to determine if the use of an ultrasonic bonecutting device is safe in the adult spinal deformity population and to compare its effectiveness in blood loss reduction by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…5 The Sonopet is primarily marketed and has been studied to be effective for orthopaedic and neurosurgical use, but facial plastic and reconstructive surgery is also listed as an application. 10,11 The "Piezoelectric System" is another ultrasonic surgical device often used by facial plastic surgeons. 12-14 However, we do not have this device at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…5 The Sonopet is primarily marketed and has been studied to be effective for orthopaedic and neurosurgical use, but facial plastic and reconstructive surgery is also listed as an application. 10,11 The "Piezoelectric System" is another ultrasonic surgical device often used by facial plastic surgeons. 12-14 However, we do not have this device at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound osteotome is the safest bone cutting tool. During operation, it does not rotate, bounce, or roll, does not entangle the surrounding soft tissue, and the bone structure is selectively removed without injury to surrounding nerve tissue (19)(20)(21)(22). Li et al (23) have reported full-endoscopic use of ultrasonic osteotome for thoracic hard discectomy, and excellent safety and surgical outcomes have been obtained.…”
mentioning
confidence: 99%